Design and performance of a microstrip reflectarray on a uniaxial substrate - Iliadis, A; Siakavara, K (Canadian journal of physics, 2002)
A design formulation of microstrip reflectarrays is presented in this paper. Previous published articles, referring to this subject, present results for reflectarrays on a uniform dielectric substrate. In this work microstrip reflectarrays with offset feed, dual polarization, and side-lobe level under control, fabricated on a uniaxial substrate were studied. The method of moments, combined with the full-wave technique, and the corresponding dyadic Green's function is used for the specification of the electromagnetic field scattered by the array. PACS No.: 84.40B